PP.LB03.05: IMPACT OF AGEING AND CARDIOVASCULAR RISK FACTORS ON VENTRICULAR REPOLARIZATION STUDIED WITH STANDARD ECG. (June 2015) - Strocchi, E.; Vitali, F.; Rosticci, M.; Rinaldi, E.R.; Cicero, A.F.G.; Malini, P.L.; Borghi, C.
Abstract : Objective: Clinical and experimental studies have shown that electrical and structural remodeling of left ventricle is associated with an increase of QT dispersion values (QTd) and that this index might provide prognostic informations. However the real value of QTd is hampered by an high inter observer and intra observer variability, and the impact of aging that by itself significantly increases QTd. Recently, new indexes of temporal dispersion of QT interval like QTVI (QT variability index) and STV (short term variability) have therefore been developed. The aim of this study was to evaluate QTd, QTVI and STV in elderly patients. Design and method: Only patients aged over eighty were enrolled in the study; patients without sinus rhythm, with previous myocardial infarction or known coronary artery disease, with electrolyte abnormalities or taking drugs known to modify the QT interval were excluded. QTd was calculated from standard good quality ECG while QTVI and STV were calculated from a longer ECG registration. For each patient we evaluated the presence/absence of traditional cardiovascular risk factors. Results: The study enrolled 40 individuals (20 men and 20 women aged between 80 and 103 years - medium age 86, 3). Based on clinical history, 26 were affected by arterial hypertension, 7 by diabetes mellitus and, after accounting for other common cardiovascular risk factors like smoking or dyslipidemia, 5 subjects could be classified at high risk (3 or more risk factors), 28 at medium risk (1–2 risk factors), and 7 at low risk (0 risk factors). The mean QT dispersion value resulted respectively 80 ms, 69, 2 ms and 40 ms in the three groups, and was higher in patients with arterial hypertension (74, 6 ms) than in normotensive subjects (48, 6 ms). Similar differences were identified also with the other indexes. Conclusions: The study shows that even in very old subjects, and therefore beyond the known effects of age, changes in ventricular repolarization studied both with QTd index and with new indexes of temporal variability like QTVI and STV reflect the cardiovascular risk profile of the patients.